Guideposts of occupational therapy. - Le Vesconte, Helen Primrose, 1896- (Heritage., 1959)
The purpose of this material is to emphasize the main avenues of occupational therapy, and to keep clear the relationship between them and their expanding periphery. It has been by design that a number of references and quotations are included.